Mapping Psychosocial Factors Associated with Online Gaming Addiction among Generation Z in Surabaya: A Qualitative Study from a Communication Science Perspective - Khansa Amelia Putri; Yuli Candrasari (International Journal of Social Sciences, Language, and Education, 2026)
This study aims to identify, map, and describe the psychosocial factors associated with online gaming addiction tendencies among Generation Z in Surabaya from a Communication Science perspective. The study focuses on how psychological needs and social relationships interact with technological characteristics in shaping patterns of excessive online gaming. An empirical descriptive qualitative approach was employed, involving eight Generation Z informants aged 14–24 years who were selected through purposive sampling based on indicators of problematic digital-media use. Data were collected through semi-structured in-depth interviews, participant observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings identified three psychological factors, namely emotional regulation and escapism, self-expression in virtual spaces, and instant gratification through game-based reward systems, as well as three social factors consisting of group conformity and mabar culture, Fear of Missing Out (FOMO), and virtual community bonding. Emotional regulation and escapism appeared among all eight informants, while social factors were dominant among five informants compared with three whose dominant patterns were psychological. The findings indicate that online gaming addiction tendencies are not solely associated with individual self-control but emerge through the interaction between psychological needs, peer relationships, virtual belonging, and technological features that sustain player engagement. The study contributes to Communication Science by integrating Uses and Gratifications, Technological Determinism, and virtual communication perspectives to explain the psychosocial dynamics underlying problematic online gaming among Generation Z.